RATE: A model‐based testing approach that combines model refinement and test execution. (18th December 2022) - Bombarda, Andrea; Bonfanti, Silvia; Gargantini, Angelo; Lei, Yu; Duan, Feng
Abstract: In this paper, we present an approach to conformance testing based on abstract state machines (ASMs) that combines model refinement and test execution (RATE ) and its application to three case studies. The RATE approach consists in generating test sequences from ASMs and checking the conformance between code and models in multiple iterations. The process follows these steps: (1) model the system as an abstract state machine; (2) validate and verify the model; (3) generate test sequences automatically from the ASM model; (4) execute the tests over the implementation and compute the code coverage; (5) if the coverage is below the desired threshold, then refine the abstract state machine model to add the uncovered functionalities and return to step 2. We have applied the proposed approach in three case studies: a traffic light control system (TLCS), the IEEE 11073‐20601 personal health device (PHD) protocol, and the mechanical ventilator Milano (MVM). By applying RATE, at each refinement level, we have increased code coverage and identified some faults or conformance errors for all the case studies. The fault detection capability of RATE has also been confirmed by mutation analysis, in which we have highlighted that, many mutants can be killed even by the most abstract models. Abstract : RATE is an approach to conformance testing based on abstract state machines (ASMs) that combines model refinement and test execution. The RATE approach consists in generating test sequences from ASMs and checking the conformance between code and models in multiple iterations, exploiting testing information to guide the model refinement.